Sempervivum davisii: phytochemical composition, antioxidant and lipase-inhibitory activities - Yusuf Uzun; Abdullah Dalar; Izabela Konczak (Taylor & Francis Group, 2017)
Context: Sempervivum davisii Muirhead (Crassulaceae) is a traditional medicinal herb from Eastern Anatolia. To date the composition of phytochemicals and physiological properties of this herb were not subjected to any research. Objective: This study identifies compounds in S. davisii hydrophilic extracts and evaluates their potential biological properties. Materials and methods: Ethanol-based lyophilized extracts were obtained from aerial parts of plant (10 g of ground dry plant material in 200 mL of acidified aqueous ethanol, shaken for 2 h at 22 °C with supernatant collected and freeze-dried under vacuum). Phytochemical composition was investigated by liquid chromatography mass spectrometry (LC-MS/MS, phenolics) and gas chromatography mass spectrometry (GC-MS, volatiles). Phenolic compounds were quantified by high-performance liquid chromatography (HPLC) and the Folin-Ciocalteu assay. Subsequently, antioxidant capacity [ferric reducing antioxidant power (FRAP), oxygen radical absorbance capacity (ORAC) assays] and enzyme inhibitory properties (isolated porcine pancreatic lipase) of the extracts were determined. Results: Polyphenolic compounds were the main constituents of lyophilized extracts, among which kaempferol glycosides and quercetin hexoside dominated. The extracts exhibited potent antioxidant (FRAP values of 1925.2-5973.3 μM Fe2+/g DW; ORAC values of 1858.5-4208.7 μM Trolox Eq./g DW) and moderate lipase inhibitory (IC50: 11.6-2.96 mg/mL) activities. Volatile compounds (nonanal, dehydroxylinalool oxide isomers, 2-decenal, 2-undecenal, 2,6-di-tetr-butylphenol) were also found. Conclusions: Phenolic compounds with the dominating kaempferol and quercetin derivatives are the sources of potent antioxidant properties of S. davisii hydrophilic extracts. The extracts exhibit moderate inhibitory properties towards isolated pancreatic lipase.